The effects of Van Hiele's phase-based learning on students' geometric achievement and attitude towards geometry - Abdullah, Abdul Halim (2014)
The process of teaching and learning geometry should be implemented more effectively because of its importance in students' daily lives. Therefore, a study that aimed to develop activities based on Van Hiele's phases of learning geometry using Geometer's Sketchpad (GSP) software was conducted. The developed activities were then incorporated into a learning kit named Geo-V. An ADDIE model was taken as reference in developing the activities and the learning kit. To study effectiveness, the developed activities were then tested for students' geometric achievement and attitude towards geometry. Quasi-experimental design was used in this study. The six-week study was conducted in a secondary school in Negeri Sembilan involving 94 students and two teachers. The students were divided into two groups, with 47 in a control group and the other 47 in a treatment group. Achievement Test (AT) and Attitude towards Geometry Survey (ATGS) were given to both groups before and after the treatment. MANOVA test was conducted to test the developed hypotheses. The results showed that there was significant difference in term of students' geometric achievement in the treatment and control groups. Also, there was no significant difference in term of students' attitude towards geometry between groups. Therefore, implementation of the activities that are based on Van Hiele's phases of learning geometry can be taken as a reference in varying the methods in teaching and learning geometry in a classroom setting.